Protection of cultural property in time of armed conflicts - Katkova, Т. G. (Honor and Law, 2019)
The analysis of international laws in the sphere of cultural property protection in time of armed conflicts is conducted. Special attention is paid to the necessity of improvement of the Ukrainian legislation in consideration of cultural property protection in accordance with International Conventions.